Determination of Benzene in Iraqi Soft Drinks - Mohammed B. Alqaraguly (Journal of Global Pharma Technology, 2018)
In this study the trace level amounts of benzene was determined in the available soft drinks(locally produced having sodium benzoate as preservatives and ascorbic acid ) in Iraqi markets, Capillary gas liquid chromatography was used in this determination which was found to give accurate results in addition to its simplicity , results was found that benzene amounts were less than 10 µg/L (which is less than the WHO level) in most samples while few others recorded little bit higher results which means reconsideration of using sodium benzoate in soft drinks should be taken into account.